Encyclopedia of Global Population and Demographics. - Ciment, James (Routledge, 2014)
This up-to-date and comprehensive encyclopedia focuses on the population in each of the 194 countries of the world. Emphasis is on the world's population at the end of the twentieth century and on predictions for the next fifty years. This will be the authoritative source of information for students, scholars, librarians, government officials, and journalists.